Characteristics of Type 1 Diabetes Among Patients Carrying the Protective HLA-DQB1*06:02 Allele - Taka, Antti‐Mathias; Härkönen,Taina; Vähäsalo, Paula; Vatanen, Tommi; Lempainen, Johanna; Veijola, Riitta; Turtinen, Maaret; Ilonen, Jorma; Knip, Mikael; Finnish Pediatric Diabetes Register (Wiley, 2025)
We set out to examine in an observational study characteristics of type 1 diabetes at the time of diagnosis among paediatric patients carrying the protective HLA class II DQB1*06:02 allele. We compared characteristics of type 1 diabetes among 5530 Finnish children aged 0-14 years diagnosed between 2003 and 2018. Seventy-five children with type 1 diabetes carried the DQB1*06:02 allele. The carriers of DQB1*06:02 allele were compared to all children with type 1 diabetes without this allele and those with a high-risk genotype. We also analysed, how does the genotype of a high-risk haplotype paired with DQB1*06:02 affect the phenotype of patients with newly diagnosed type 1 diabetes. Carriers of the DQB1*06:02 allele were diagnosed at an older age than those with any other HLA class II genotype (p = 0.003) or the high-risk genotype (p < 0.001). After adjusting the results for age and sex, no significant differences in clinical markers were observed. Glutamic acid decarboxylase autoantibody (GADA) levels were higher among carriers of DQB1*06:02 when compared to those with other genotypes (p = 0.033). Having a high-risk haplotype paired with DQB1*06:02-positive haplotype was associated with higher levels of islet antigen 2 autoantibodies (IA-2A) (p < 0.001) and somewhat shorter duration of symptoms (p = 0.043). The association between the protective DQB1*06:02 allele and an older age at diagnosis as well as higher levels of GADA at diagnosis of type 1 diabetes was confirmed. The effects of the DQB1*06:02-positive haplotype seem to dominate when paired with a high-risk haplotype.